Academic support through tutoring, guided learning, and learning diaries in the context of the COVID-19 pandemic: an experimental model for master’s students - Dumitru, Cristina; Stan, Maria Magdalena; Dumitru, Georgiana (Frontiers in Education, 2024)
Engaging students in co-planning their learning paths, peer cooperation, tutoring and network building in an inclusive and project-based environment has been proven to be associated with a higher impact on academic and professional success for students. However, university teachers find it challenging to offer guidance and academic supervision to optimize their students' learning, or they may not consider it crucial to practice and facilitate self-guidelines skills. Based on an experimental design methodology, this study investigated how, in the new context of shifting to online learning space, universities should adapt to provide a collaborative learning environment, peer-tutoring, and academic supervision as forms of learning and teaching. The findings showed direct positive effects on the level of engagement (VI; M = 23.18, SD = 5), higher interest and dedication to the learning process (DE: M = 26.93, SD = 3.21), and better concentration and enthusiasm while studying (AB, M = 24.83, SD = 8.52).